Nerve cells and animal behaviour - Young, David 1942 February 25- (Cambridge University Press, 1999)
This new edition of Nerve Cells and Animal Behaviour has been updated and expanded by Peter Simmons and David Young in order to take into account more recent advances while still maintaining the accessibility of the book to university students. The book introduces the reader to the way in which nervous systems of animals control behaviour without assuming any prior knowledge of neurophysiology. Using a carefully selected series of behaviour patterns students are taken from an elementary-level introduction to a point where sufficient detail has been assimilated to allow a satisfying insight into current research on how nervous systems control and generate behaviour. Only examples where it has been possible to establish a clear link between the activity of particular nerve cells and a pattern of behaviour have been used. This book is essential reading for students of zoology, psychology and physiology and serves as a clear introduction to neuroethology.